UNDERSTANDING JUCHE IDEOLOGY THROUGH PSYCHOLOGY OF PEACE AND CONFLICT IN NORTH KOREA - Mega Nisfa Makhroja (UIN ALAUDDIN MAKASSAR, 2020)
This paper examined moral justification due to Juche's ideology in North Korea as the main reason for the survival of the authoritarian regime and caused violence. By using Moral Justification analysist from Psychology of peace and conflict, this paper explain how Juche Ideology affected to Violence, How intervention toward north Korean Conflict from international society, and possible scenario to implemented in North Korea. However, North Korean conflict not only affected their national issue, but also international level. High number of Human Right Violation in this country can be understood by psychological of peace and conflict studies.